Distribution of antibiotics in water, sediments and biofilm in an urban river (Córdoba, Argentina, LA). (15th January 2021) - Valdés, M. Eugenia; Santos, Lúcia H.M.L.M.; Rodríguez Castro, M. Carolina; Giorgi, Adonis; Barceló, Damià; Rodríguez-Mozaz, Sara; Amé, M. Valeria
Abstract: In this study, we evaluated the distribution of up to forty-three antibiotics and 4 metabolites residues in different environmental compartments of an urban river receiving both diffuse and point sources of pollution. This is the first study to assess the fate of different antibiotic families in water, biofilms and sediments simultaneously under a real urban river scenario. Solid phase extraction, bead-beating disruption and pressurized liquid extraction were applied for sample preparation of water, biofilm and sediment respectively, followed by the quantification of target antibiotics by UPLC-ESI-MS/MS. Twelve antibiotics belonging to eight chemical families were detected in Suquía River samples (67% positive samples). Sites downstream the WWTP discharge were the most polluted ones. Concentrations of positive samples ranged 0.003-0.29 µg L -1 in water (max. cephalexin), 2-652 µg kg -1 d.w. in biofilm (max. ciprofloxacin) and 2-34 µg kg -1 d.w. in sediment (max. ofloxacin). Fluoroquinolones, macrolides and trimethoprim were the most frequently detected antibiotics in the three compartments. However cephalexin was the prevalent antibiotic in water. Antibiotics exhibited preference for their accumulation from water into biofilms rather than in sediments (bioaccumulation factors > 1, 000 L kg -1 d.w. in biofilms, while pseudo-partition coefficients in sediments < 1, 000 L kg -1 d.w. ). Downstream the WWTP there was an association of antibiotics levels in biofilms with ash-free dry weight, opposite to chlorophyll-a (indicative of heterotrophic communities). Cephalexin and clarithromycin in river water were found to pose high risk for the aquatic ecosystem, while ciprofloxacin presented high risk for development of antimicrobial resistance. This study contributes to the understanding of the fate and distribution of antibiotic pollution in urban rivers, reveals biofilm accumulation as an important environmental fate, and calls for attention to government authorities to manage identified highly risk antibiotics. Graphical abstract: Image 1 Highlights: Different antibiotic families found in water, biofilms and sediments. Fluoroquinolones, macrolides and trimethoprim are the most frequently detected. Sites downstream the wastewater treatment plant discharge were the most polluted. Antibiotics accumulate in biofilms rather than in sediments. Cephalexin, clarithromycin and ciprofloxacin pose environmental/resistance risk.